Pengaruh Modal Kerja, Biaya Produksi, Penjualan dan Total Hutang Terhadap Laba Bersih Perusahaan: Studi Empiris pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Rika Aprianti; Retno Fuji Oktaviani (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
This research aims to determine the effect of Working Capital, Production Costs, Sales and Total Debt on Net Profit in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2019-2023 Period. The type of research used is quantitative using secondary data, namely financial reports. The sampling technique used was purposive sampling. Of the 95 companies, only 24 companies met certain criteria. The analysis model used is multiple linear regression analysis which was tested with IBM Statistics Product and Solution (SPSS) Version 25. The research results show that partially Working Capital has a positive and significant effect on Net Profit. Production and Sales Costs do not have a significant effect on Net Profit. Total Debt has a positive and significant effect on Net Profit.